A Study On Perception Of Performances Appraisal System In The Malaysian Army - Ramayanan, Morgan AL P (2008)
The purpose of this descriptive research is to provide a comprehensive clarification with regards to the numerous factors in relation to Performance Appraisal that must be critically analyzed and addressed by the Human Resources Department in the Malaysian Army in order to improve its degree of Performance Appraisal implemented since 1985.